2022
DOI: 10.3762/bjoc.18.93
|View full text |Cite
|
Sign up to set email alerts
|

On Reuben G. Jones synthesis of 2-hydroxypyrazines

Abstract: In 1949, Reuben G. Jones disclosed an original synthesis of 2-hydroxypyrazines involving a double condensation between 1,2-dicarbonyls and α-aminoamides upon treatment with sodium hydroxide at low temperature. This discovery turned out to be of importance as even today there are no simple alternatives to this preparation. Across the years, it was employed to prepare 2-hydroxypyrazines but some of its limits, notably regioselectivity issues when starting from α-ketoaldehydes, certainly hampered a full-fledged g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Prior investigations clearly demonstrated that glycine (5) and glyoxylic acid (8) do not serve as direct precursors to 3-isobutyl-2-methoxypyrazine (IBMP, 1). Instead, they are deemed to act as C 1 -building blocks, suggesting that they are first metabolized before they are incorporated into 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior investigations clearly demonstrated that glycine (5) and glyoxylic acid (8) do not serve as direct precursors to 3-isobutyl-2-methoxypyrazine (IBMP, 1). Instead, they are deemed to act as C 1 -building blocks, suggesting that they are first metabolized before they are incorporated into 1.…”
Section: Resultsmentioning
confidence: 99%
“…As many pesticides, pharmaceuticals and flavorings are pyrazine‐based, they are also synthesized chemically in industry [4–6] . The pyrazine ring can be synthesized using various routes mainly by direct ring closure such as the two‐step synthesis starting with a condensation of a 1,2‐diketone with a 1,2‐diamine (Scheme 1A) or the spontaneous intramolecular α‐aminoketone‐cyclization (Scheme 1B) [4,5,7,8] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation